Modelling and Simulation of Multi-Rate Multi-Service Traffic in the Presence of Mobility - Juarez, Jesus M. (2006)
A multi-service traffic model is proposed, and its validation is achieved by using event-based simulation results. In the single-service case, theoretical and experimental results for ON-OFF blocking probability are close to each other, and there is an almost perfect concordance between theoretical and simulation values when the average sojourn time in cells is equal to the average holding time. In the multi-service case, the behaviour is not exactly the same but a coherent behaviour is achieved for an average traffic per user up to 0.10 Erl.